2011
DOI: 10.3390/ma4010327
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Based Fabrication of Organic/Inorganic Composite Gel Material

Abstract: Biomaterials containing components similar to the native biological tissue would have benefits as an implantable scaffold material. To obtain such biomimetic materials, cells may be great contributors because of their crucial roles in synthetic organics. In addition, the synthesized organics—especially those derived from osteogenic differentiated cells—become a place where mineral crystals nucleate and grow even in vitro. Therefore, to fabricate an organic/inorganic composite material, which is similar to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…The calcium content in the fibrin gels showed dramatic increases between 20 and 30 days of culture and then further increased slightly by the end of the culture period. These results are consistent with our previous study, which demonstrated that mineral deposition started after 20 days in floating fibrin gels with BMSCs . OPN, one of the major noncollagenous proteins, is known to be correlated with bone remodeling .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The calcium content in the fibrin gels showed dramatic increases between 20 and 30 days of culture and then further increased slightly by the end of the culture period. These results are consistent with our previous study, which demonstrated that mineral deposition started after 20 days in floating fibrin gels with BMSCs . OPN, one of the major noncollagenous proteins, is known to be correlated with bone remodeling .…”
Section: Discussionsupporting
confidence: 93%
“…These results are consistent with our previous study, which demonstrated that mineral deposition started after 20 days in floating fibrin gels with BMSCs. 22 OPN, one of the major noncollagenous proteins, is known to be correlated with bone remodeling. 23 To further examine the composition of the osteogenic-induced fibrin gels, the OPN amounts were determined at different culture times by ELISA.…”
Section: Discussionmentioning
confidence: 99%
“…This idea is supported by previous studies indicating slower mineral precipitation of differentiated MSCs in a 3D fibrin gel culture. 25 MSCs are known to differentiate multiple cell types not only chondrocyte but also osteoblast, myoblast, and adipocyte. 26 Since the MSC cell ball was cultured in the osteogenic differentiation medium in this study, osteopontin and osteocalcin, the osteogenic differentiation marker of cells, were also evaluated.…”
Section: Cell Differentiation Of Mscs In the Cultured Cell Ballmentioning
confidence: 99%
“…Composite materials have found applications in many different fields, such as semiconductors, 123 solar cells 124 and biomedicine. 125,126 PPDs have been used as rigid spacers and cross-linkers of inorganic nanoparticles in a number of composite materials with different applications.…”
Section: Self-assembly To Nanofibers and Nanorodsmentioning
confidence: 99%